Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Dan Sewa Tempat Usaha Di Pasar Tugu Perumda Pasar Jaya DKI Jakarta - Sumidartiny, Ai Netty; Witya, Naufal Adilah (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This research aims to analyze the marketing strategies employed by Tugu Market, Perumda Pasar Jaya, DKI Jakarta, to enhance sales and business rental. It also aims to identify the challenges faced by Tugu Market, Perumda Pasar Jaya, DKI Jakarta, and the efforts that will be made to improve sales and business rental. The research adopts a qualitative approach with a descriptive design. Data analysis follows the Miles and Huberman model, which includes data presentation, data reduction, and data verification. Data is collected through observation, interviews, and documentation. The research findings are described using SWOT analysis, market segmentation, target market, and market positioning. The results indicate that the marketing strategies implemented by Tugu Market, Perumda Pasar Jaya, DKI Jakarta, to increase sales and business rental align with general marketing methods. These strategies involve formulating the target market using segmentation, targeting, and positioning strategies, as well as employing the 7Ps marketing mix (Product, Price, Place, Promotion, People, Process, Physical Evidence). The challenges faced include a shortage of manpower, intense competition, and a less strategic location. Efforts to address these challenges involve offering high-quality business spaces at affordable prices, promoting available business spaces through internet networks and social media platforms such as Instagram and Twitter, obtaining approval from the Head Office’s Board of Directors, and providing various Services to consumers, including security, cleanliness, maintenance, and care.